Novel Usefulness of M2BPGi for Predicting Severity and Clinical Outcomes in Hospitalized COVID-19 Patients - Mikyoung Park; Mina Hur; Hanah Kim; Chae Hoon Lee; Jong Ho Lee; Hyung Woo Kim; Minjeong Nam; Seungho Lee (Diagnostics)
Background/Objectives: Mac-2 binding protein glycosylation isomer (M2BPGi) is a novel biomarker for liver fibrosis, and its prognostic role has never been explored in coronavirus disease 2019 (COVID-19). We compared the M2BPGi level simultaneously with age, severe/critical disease, the sequential organ failure assessment (SOFA) score, and the National Early Warning Score 2 (NEWS2) in a total of 53 hospitalized patients with COVID-19 (mild/moderate [n = 15] and severe/critical [n = 38]). Methods: M2BPGi levels were measured using the HISCL M2BPGi assay (Sysmex, Kobe, Japan) in an HISCL-5000 analyzer (Sysmex), and clinical outcomes were analyzed according to M2BPGi and the clinical variables, using the receiver operating characteristic (ROC) curve, Kaplan–Meier survival, and Cox proportional hazards regression analyses. Results: M2BPGi levels differed significantly according to disease severity, 30-day mortality, and 60-day mortality (p = 0.045, 0.011, and 0.002, respectively). In the ROC curve analysis, the M2BPGi, age, SOFA score, and NEWS2, except for severe/critical disease, significantly predicted clinical outcomes (all p < 0.01). In the survival analysis, the hazard ratios of M2BPGi added to each clinical variable were higher than that of each clinical variable alone, and M2BPGi was the only independent prognostic factor for the mortality. Conclusions: This study demonstrated that M2BPGi may be a useful biomarker for assessing disease severity and clinical outcomes in hospitalized COVID-19 patients. Combined with conventional clinical assessment, M2BPGi would provide objective and valuable information for prognosis prediction in these critically ill patients. Further studies are warranted to extend its utility in other clinical settings.